Unsystematic Risk Management based on Financial Literacy as a Supporting Factor in Investment Decisions - Riawan Riawan; Wahna Widhianingrum; Wijianto Wijianto (Universitas Muhammadiyah Ponorogo, 2024)
This research examines financial literacy's influence on investment decisions through unsystematic risk management. The data source used in this research is primary data obtained through a questionnaire. The sampling technique used was purposive sampling, using sample criteria to enter as a research sample. This research involved 88 respondents as research samples. The analytical tool used to carry out statistical tests is SmartPLS. This study found that financial literacy and unsystematic risk management simultaneously had a significant positive effect on investment decisions. Unsystematic risk management has a significant positive effect on investment decisions. Furthermore, unsystematic risk management can mediate the relationship between financial literacy and investment decisions. This study highlights investor behavior in making investment decisions using the theory of planned behavior approach.